Effects of operational parameters on methane production and microbial community in anaerobic digesters fed with cow manure and barley - Tutal, Bilgesu. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2017., 2017)
In this study, effects of temperature (mesophilic vs. thermophilic), inoculum to substrate (I:S) ratios and different types of inoculums on methane production and microbial community profiles were investigated in anaerobic batch tests. The highest specific methane yield (278±12 mL CH4/g VS) was found in the digester containing anaerobic seed sludge and cow rumen fluid as supportive inocula which was operated with an I:S ratio of 1:2 at mesophilic temperature, followed by the thermophilic digester (259±12 mL CH4/g VS ) inoculated only with anaerobic seed sludge with the same I:S ratio. The phylum Firmicutes, Bacteroidetes and Proteobacteria were major bacterial phyla for all sets. Hydrogenotrophic methanogenesis was favored in all digesters as the relative abundance of hydrogenotrophic methanogens was higher than that of acetotrophic methanogens. The most dominant methanogenic Archaea was Methanobacterium sp. in the digesters inoculated only with anaerobic seed sludge; whereas, Methanobrevibacter spp. dominated the digesters contained the rumen fluid. The total 16S rDNA copy number of bacteria and Archaea decreased in time for all digesters The results show that the methane yield can be improved with the combination of different types of inocula instead of additional energy input in thermophilic anaerobic digesters.
Keywords: Methane.; Microbial biotechnology.